28 years later. The Bone Temple [videorecording (Blu-Ray)] - Hildur Guðnadóttir (Sony Pictures Home Entertainment, 2026)
"In a continuation of the epic story, Dr. Kelson finds himself in a shocking new relationship--with consequences that could change the world as they know it--and Spike's encounter with Jimmy Crystal becomes a nightmare he can't escape. In the world of The Bone Temple, the infected are no longer the greatest threat to survival--the inhumanity of the survivors can be stranger and more terrifying."--